Condição física dos bombeiros militares do curso de formação de soldado 2013 da região metropolitana de Curitiba - PR - Kindinger, Bruno Augusto (2015)
Credibility led by firefighters with 92% confidence the population of 15 countries among the 25 studied in the world by GFK Verien is one of the important reasons to analyze the physical condition of professional. The aim of this study was to evaluate the physical profile of civilians who join the corporation and later military training. Participated, 13 males, firefighters who have done training course for soldiers in 2013, the metropolitan region of Curitiba, specifically pertaining to the course 6 Grouping of Paraná Firefighters, aged 21-32 years. Was collected from the corporate database the results of the physical fitness test (TAF) consisting of shuttle run test (speed race), arm flexion on high bar and 12 minutes of running, made during the course (2 months the beginning) and so formed (three months after graduation). The following is an annual schedule of evaluation of the military in order to keep the military always fit and well conditioned, the implementation of TAF is made every six months. Research has shown that newly trained firefighters kept the agility, evaluated by the shuttle run test, increased the strength of upper limbs, evaluated by horizontal bar test (p <0.05), and decreased cardiorespiratory fitness, measured by the running test 12 minutes (p <0.05). It follows, therefore, that after the stressful training process, there was detraining as to cardiorespiratory and continuous maintenance and enhancement of strength of the upper members. The professional activity that the military firefighter plays in society requires physical standards above the limit considered "normal" in any context. So the constant training of physical valences are essential for health and Fireman quality of life as well as for the perfect performance of their duties. It is suggested that the implementation of programs to promote the health and practice of general and specific physical activities of professional function.